The Islamic challenge politics and religion in Western Europe - Klausen, Jytte (Oxford ; New York, N.Y. : Oxford University Press, 2005)
Who are Europe's Muslim leaders? How do they view Islamic integration into European society and politics? Based on 300 interviews with Muslim leaders, this innovative book tackles big questions to reveal what Muslim leaders in Europe really want and the myriad ways in which Islam can become a European religion. - ;The voices in this book belong to legislators, local officials, doctors and engineers, educators and intellectuals, lawyers and social workers, owners of small businesses, translators, and community activists. They are also all Muslims, who have decided to become engaged in political.
Introduction : Islam in Europe -- 1. Europe's new Muslim political elite -- 2. How do Muslim leaders see the problems? -- 3. Belief and politics -- 4. From conflict to culture war -- 5. Christian and Muslim Europe -- 6. Sexual politics and multiculturalism -- Conclusion : liberal Muslims and the emergence of European Islam -- Appendix: Methodology.
Includes bibliographical references (pages 223-229) and index.
Print version record.
Keywords: Muslims -- Europe, Western; Islam and state -- Europe, Western; Muslims; SOCIAL SCIENCE -- Discrimination & Race Relations; Islam and state; Muslims; Europe, Western; Islam; Politieke conflicten; Electronic books